When workplace unionism in global value chains does not function well: exploring the impediments - Louche, Céline (Journal of business ethics, 2020)
Improving working conditions at the bottom of global value chains has become a central issue in our global economy. In this battle, trade unionism has been presented as a way for workers to make their voices heard. Therefore, it is strongly promoted by most social standards. However, establishing a well-functioning trade union is not as obvious as it may seem. Using a comparative case study approach, we examine impediments to farm-level unionism in the cut flower industry in Ethiopia. For this purpose, we propose an integrated framework combining two lenses, namely a vertical one (governance and structure of global value chains) and a horizontal one (socio-economic context). We identify 10 impediments that point to three major dimensions contributing to unionisation. These three dimensions include awareness of and interest from workers, legitimacy of trade unions, and capacity of trade unions to act. Furthermore, our results suggest that private social standards may, in certain cases, be counterproductive for the efficient functioning of trade unions. Although we argue that there is no ‘quick fix’ solution to weak workplace unionism at the bottom of global value chains, we stress the importance of considering the dynamics of, and interactions between, the impediments when designing potential support measures that mitigate negative impacts.